Research Status of Self-healing Concrete. (January 2019) - Wang, Wei; Zhong, Tieyi; Wang, Xiaoxue; He, Zhenyu
Abstract: Through collecting, sorting and analyzing the domestic and foreign references of self-healing concrete research, this paper has summarized the experimental research methods and results of different types of self-healing concrete in recent years, and expounded the mechanism of its action. Self-healing concrete types include self-healing concrete based on concrete itself, self-healing concrete based on permeable crystal repair technology, self-healing concrete based on shape memory alloy, self-healing concrete based on bionic self-repair and self-healing concrete based on microbial. Finally, the existing problems of self-healing concrete are put forward, and the shortcomings of self-healing concrete need to be further strengthened.